PENGARUH SELF REGULATED LEARNING DAN INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP PERILAKU PROKRASTINASI AKADEMIK - Intan Diya Fadilah; Gugum Gumilar; Edi Fitriana Afriza (JOURNAL SAINS STUDENT RESEARCH, 2025)
The problem in this study is that there are still many students who procrastinate when doing assignments. This study aims to determine the influence of self-regulated learning and the intensity of smartphone use on academic procrastination. This study uses a quantitative method with an explanatory design. The population is 466 students in grades XI-XII Social at SMAN 1 Sindangkasih, with a sampling technique using Simple Random sampling so that a total of 215 students were obtained. The analysis techniques used were normality test, linearity test, multicollinearity test, heteroskedasticity test, and multiple linear analysis. Hypothesis testing uses t-test and F-test. The results of the study showed that: 1) There was a significant influence of self-regulated learning on academic procrastination with a significance value of 0.010. 2) There was a significant influence of the intensity of smartphone use on academic procrastination with a significance value of 0.000. 3) There was a significant effect between self-regulated learning and the intensity of smartphone use on academic procrastination with a significance value of 0.000.